Evidence for the baryonic decay B [bar] 0 → D0 [lambda] [lambda] [bar] - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
Evidence is presented for the baryonic B meson decay ¯B0→D0Λ¯Λ based on a data sample of 471×106 B¯B pairs collected with the BABAR detector at the PEP-II asymmetric e+e− collider located at the SLAC National Accelerator Laboratory. The branching fraction is determined to be B(¯B0→D0Λ¯Λ)=(9.8+2.9−2.6±1.9)×10−6, corresponding to a significance of 3.4 standard deviations including additive systematic uncertainties. A search for the related baryonic B meson decay ¯B0→D0Σ0¯Λ with Σ0→Λγ is performed and an upper limit B(¯B0→D0Σ0¯Λ+¯B0→D0Λ¯Σ0)<3.1×10−5 is determined at 90% confidence level.